Unusual case of cleft hand - B Parag Sahasrabudhe; D Madhuri Kulkarni (Indian Journal of Plastic Surgery)
we present a case of a six-year-old male child with cleft hand deformity involving the dominant right hand. it was a rare case of atypical cleft hand with no missing tissue but cleft extending to metacarpal level and associated hypoplasia of thumb and index finger. as per manske′s classification of cleft hand our patient belongs to the class iii variety. there was associated malposition of the index finger with absence of first web space and syndactly of thumb and index finger at the metacarpal level. a modified snow-littler procedure was planned. the surgical plan involved closure of cleft, release of thumb and index finger syndactly and reconstruction of the first web space. the functional outcome was good considering hypoplasia of the index finger and thumb. depending upon the function of the thumb tendon transfers can be planned to augment thumb function at a later date along with correction of rotational deformities of the index and middle finger.